(untitled) (American Journal of Islam and Society, 2009)
This work by a leading French Islamicist is both an analysis of Islam, secularism, and society in Europe, as well as a prescription for its leaders on how to “correct” their wrongheaded policies with regard to their Muslim minorities based on this analysis. This might seem unduly arrogant on Olivier Roy’s part, but his past landmark books do seem to commend the perspicacity of his views on the subject, and most of all, The Failure of Political Islam (Harvard University Press: 1994) and Globalized Islam: The Search for the New Umma (Hurst: 2004). On one level, Roy is focused on France: how one might begin to mitigate the polarization of the French elites in the wake of forbidding the veil in public places and the violence of the 2005 riots in the poorest – mostly Muslim – suburbs of Paris. Indeed, the first chapter is devoted to the historical roots of France’s virulent version of state-enforced secularism (laïcité). But on another level, this is a work rich in theoretical analysis, widening its insights to Britain and the United States and their “common law” version of laïcité, as well as providing a new theory to the sociology of religion. The intensity of the French debate raises important questions. “The campaign of Islamophobia we are witnessing today is involved in the reshaping of the French political and intellectual landscape” (p. 2). How so? The Christian Right and the Extreme Right’s suspicion of Islam is now shared by a sizable portion of the Left, which has reacted with fear to the French Muslim community’s new and outspoken rhetoric. School girls want to wear the veil out of pride. And this new Islamic discourse has been promoted both by the “bearded Salafist preacher” and the suave intellectual embodied by Tariq Ramadan ...